Pengasuhan Lintas Generasi di Indonesia: Studi Kualitatif tentang Peran Kakek-Nenek dalam Pembentukan Nilai Anak - Nahda Khoirunnisa; Wanodaya Kusumastuti; Eko Harianto (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to describe the role of grandparents in childcare within multigenerational families in Indonesia’s changing social context. A descriptive qualitative approach was employed, with data collected through in-depth interviews and observations involving grandparents actively engaged in caregiving. Data analysis followed stages of reduction, presentation, and conclusion drawing to identify key themes from participants’ experiences. The findings reveal four significant themes: intergenerational communication and affection, positive discipline without violence, child safety at home, and play activities that preserve local cultural values. These themes illustrate that grandparents serve not merely as helpers but as central figures in transmitting moral values, fostering discipline, and maintaining family traditions. The nurturing relationship they establish through empathy and emotional closeness reflects harmony between traditional family wisdom and modern parenting needs. This study underscores the importance of empowering grandparents through reflective learning materials or guidance that enable them to practice caregiving with wisdom, compassion, and cultural relevance.